Integration of EMI (English as Medium of Instruction) through a collaborative teaching scheme to improve the quality of teachers - Affandi, Akhmad; Fadlih, Andi Muhammad; Nastah, Mardiyanah; Fakhri , M. Miftach; Mursalim, Muliana (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2025)
This community service activity aims to improve teachers' ability to implement Collaborative Teaching based on English Medium Instruction (EMI) at SMA Negeri 5 Gowa. The program was carried out using a Participatory Action Research (PAR) approach involving 23 teachers from various subjects. The instrument was in the form of a pre-posttest questionnaire with 20 Likert scale statements (1–5) which included four dimensions: EMI ability, understanding collaborative teaching, collaborative implementation of collaboration, and effectiveness and feedback. The results of the analysis showed a significant increase with an average of +1.27 points in all dimensions. The biggest improvement was in the aspect of collaboration implementation (+1.29), particularly the skill of designing a 20-minute micro-lesson and providing clear collaborative instructions. These findings confirm that the EMI-based Collaborative Teaching Scheme is able to strengthen teacher confidence, increase pedagogical understanding, and foster a peer-mentoring culture in schools. The use of PAR as a framework of service has proven to be effective because it places teachers as active partners in the planning, implementation, and reflection process. The program not only improves short-term skills, but also forms an ecosystem of continuous reflective learning. Thus, this model has the potential to be replicated in other secondary schools as a strategy to improve the quality of education that is in line with the Impact Campus policy and SDGs targets